Pterygoplichthys ambrosettii (Holmberg, 1893) (Siluriformes: Loricariidae): invasão, história de vida e impactos sobre o funcionamento do ecossistema. - Silva, Jislaine Cristina da (2019)
Biological invasions are among the greatest threats to global biodiversity, and in Brazil the introduction of non-native fish has become increasingly common. Due to this problem, studies on the biology of non-native species are necessary for the understanding of aspects related to biological invasions and successful establishments. However, the factors related to these processes still lack information, fact observed for the species of invasive fish Pterygoplichthys ambrosettii. This species is considered to be one of the most abundant in the floodplain of the Upper Paraná River, and its introduction is increasingly widespread, and yet much of its biology and natural history remain untested. Thus, the general objective of this thesis was to analyze aspects related to invasion, life history and impacts on the ecosystem by P. ambrosettii, in the upper Paraná River basin. First, the chronology of invasion of this species was analyzed by means of long-term data (1983-2017), in order to identify the main route or means of dispersion of this species in the basin. The second study aimed to know the life history of P. ambrosettii and its relations with its invasion and establishment. The third study provides a detailed description of the embryonic, larval and juvenile development, obtained from P. ambrosettii induced reproduction. The fourth study, through an experimental approach, analyzed the effect of the abundance of P. ambrosettii on the functioning of the invaded ecosystem. The historical invasion of P. ambrosettii confirms its status as introduced in the upper Parana River, possibly through aquarism, began to occur in the region as of 1997. It is currently dispersed and established throughout the basin, presenting high potential for invasiveness, which was confirmed in this study. In general, aspects of life history presented by this suckermouth armored catfishes, such as 1: 1 sexual ratio, moderate body size and fecundity, first maturation size, parental care, long embryonic development, large eggs and precocious larvae, maximize offspring survival, and guarantee their recruitment. In addition, specific egg characteristics, such as the ability to manage the use of endogenous oxygen and the adhesiveness, which reduce the friction within the nest, also cooperate for the resistance of the offspring, and consequently of the species. In addition to all the advantages already imposed by the biology of P. ambrosettii, it was observed that in high abundances, this can promote consistent effects on the cycling of nutrients in the ecosystem. The abiotic variables pH, dissolved oxygen and electrical conductivity were altered by treatments, as well as the primary productivity (chlorophyll-a and aquatic macrophytes), which presented high concentrations and biomass, as a function of the increase of nutrients (nitrogen and phosphorus) in the column of water. On the other hand, a reduction in the density and composition of protozooplankton were caused directly or indirectly by changes in water quality. At the end of the study, specific conditions of a eutrophic environment were observed. Thus, in view of the prospects of an invasive species, P. ambrosettii showed a very expressive model, with singular characteristics of life history and disturbances on the communities and functional ecosystem structure.